Barcode recognition system - Hashim, N M Z; Ibrahim, N A; Saad, N M; Sakaguchi, F; Zakaria, Z (IJETTCS, 2013)
Barcode became essential elements in sales and products services due to importance of keeping records of all items in on place. For this purpose, there are many methods implemented to make the barcode reading process became easier to users. This project is to develop a barcode recognition system by using image processing. The system will be able to read barcode through an image and the system capable to capture the image by using a webcam. This project will be using MATLAB software program to develop the system and it will integrate with webcam or digital camera. System will analyse the image and then display on the Graphical User Interface (GUI) the barcode type, data and size of the image. System is designed to recognize different types of barcode and display the data once the barcode image is captured. System also is to provide convenience way of observing data from the barcode with lower costing compared by using the electronic barcode scanners. This system can be used anytime and anywhere by the user who likes to observe the data represented by the barcode numbers without going any places providing the barcode scanner services. As the result, the project has been developed smoothly and perfectly. For the future system development, it is suggested that the system also should consist a slider so that the user would able to control the brightness of the image which captured by webcam.